2017
DOI: 10.1152/jn.00663.2016
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of corticospinal input to the legs by arm and leg cycling in people with incomplete spinal cord injury

Abstract: The spinal cervico-lumbar interaction during rhythmic movements in humans has recently been studied; however, the role of arm movements in modulating the corticospinal drive to the legs is not well understood. The goals of this study were to investigate the effect of active rhythmic arm movements on the corticospinal drive to the legs () and assess the effect of simultaneous arm and leg training on the corticospinal pathway after incomplete spinal cord injury (iSCI) ( 2). In , neurologically intact (NI) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…However, this facilitation was not present during arm cycling for individuals with incomplete SCI prior to A&L cycling training (Zhou et al, 2017). Excitingly, 12 weeks of A&L cycling training reengaged these connections by significantly increasing the amplitude of the motor evoked potential (MEP) in the tibialis anterior muscle compared to baseline levels prior to the intervention (Zhou et al, 2017). Furthermore, disruptions in cervico-lumbar connectivity, which are noted after both incomplete SCI and chronic stroke, can be reduced by the simultaneous A&L cycling paradigm (Klarner et al, 2016b;Zhou et al, 2018b).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, this facilitation was not present during arm cycling for individuals with incomplete SCI prior to A&L cycling training (Zhou et al, 2017). Excitingly, 12 weeks of A&L cycling training reengaged these connections by significantly increasing the amplitude of the motor evoked potential (MEP) in the tibialis anterior muscle compared to baseline levels prior to the intervention (Zhou et al, 2017). Furthermore, disruptions in cervico-lumbar connectivity, which are noted after both incomplete SCI and chronic stroke, can be reduced by the simultaneous A&L cycling paradigm (Klarner et al, 2016b;Zhou et al, 2018b).…”
Section: Introductionmentioning
confidence: 81%
“…The torso was restrained using a seat belt, and the experimental arm (left) was secured in a fixed pronated position using straps into a secure brace, embedded with a force sensor (Neurolog, Hertfordshire, United Kingdom). The left arm was chosen to be comparable to previous investigations from the same laboratory (Zhou et al, 2017(Zhou et al, , 2018b. The effect of leg cycling on upper limb reflex responses between the right and left limbs, and the relative difference between experimental conditions is expected to be similar regardless of which arm is used (Zehr et al, 2007;Nakajima et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would suggest that functional changes in corticospinal pathways may occur at multiple levels, not only at those directly involved in generating and controlling the limbs performing the movements. In support of such mechanisms are the findings of a work performed by Zhou et al (2017) that demonstrate changes in the motor-evoked potentials in the lower limb in neurologically intact individuals and patients with incomplete spinal cord injury following arm cycling alone or simultaneous arm and leg cycling, respectively. Our study adds to this body of knowledge, by providing evidence that AET can improve the synergistic action of an agonist and antagonist neuromuscular networks in PD.…”
Section: Discussionmentioning
confidence: 90%
“…This is supported by the work of Zehr and colleagues, who showed that motor evoked potentials (MEPs) elicited in non-exercising arm muscles are facilitated during submaximal leg cycling 5 . Similarly, during low-intensity cycling using the arms, MEPs measured in the non-exercising vastus lateralis (leg) muscle also increased 6 . Taken together, these findings indicate that as facilitation was observed in non-exercising muscles, exercise contributes to increasing a state of ‘global corticospinal excitability’ (CSE).…”
Section: Introductionmentioning
confidence: 92%